2012
DOI: 10.1007/s12035-012-8355-9
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Scopolamine-Induced Memory/Synaptic Disorder by Rescuing EPACs/miR-124/Egr1 Pathway

Abstract: Alzheimer's disease (AD) is the most prevalent type of dementia in elderly people. There are decreased melatonin levels in the serum of AD patients, and melatonin supplements are able to reverse AD pathology and memory deficits in many animal experiments and clinical trials. However, the underlying mechanism regarding how melatonin rescues the AD-like memory/synaptic disorder remains unknown. Here, we use the Morris water maze, step-down inhibitory avoidance task, in vivo long-term potentiation recording, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 40 publications
6
69
0
Order By: Relevance
“…Dose of SCO was selected based on previous studies (Wang et al 2013;Yan et al 2014). The control mice (n = 14 at each point in time) were injected with the same volume of saline (pH 7.4).…”
Section: Scopolamine Treatmentmentioning
confidence: 99%
“…Dose of SCO was selected based on previous studies (Wang et al 2013;Yan et al 2014). The control mice (n = 14 at each point in time) were injected with the same volume of saline (pH 7.4).…”
Section: Scopolamine Treatmentmentioning
confidence: 99%
“…Suppression of miR-124 restored normality in all measures. A study of memory amelioration by melatonin also found Epac and miR-124 modulation associated with improvement (Wang et al 2013). In contrast, another recent study reported Epac activation in the nucleus accumbens interfered with conditioned place preference learning (Park et al 2014).…”
mentioning
confidence: 99%
“…AD-like memory deficits were investigated in a rat model using scopolamine toxicity [190]. The toxin caused decreases in EPAC1, EPAC2 (cAMP-regulated guanine nucleotide exchange factor-1, -2) and RagA (Ras-related GTP-binding protein), changes that led to an increase in miR-124 and a decline of its target, Egr1 mRNA (early growth response protein 1, alias NGFI-A, nerve growth factor-induced protein A).…”
Section: The Central Nervous System Neurogenesis Neuropsychiatrimentioning
confidence: 99%
“…The toxin caused decreases in EPAC1, EPAC2 (cAMP-regulated guanine nucleotide exchange factor-1, -2) and RagA (Ras-related GTP-binding protein), changes that led to an increase in miR-124 and a decline of its target, Egr1 mRNA (early growth response protein 1, alias NGFI-A, nerve growth factor-induced protein A). Melatonin reversed all these changes and attenuated memory and synaptic deficits [190]. …”
Section: The Central Nervous System Neurogenesis Neuropsychiatrimentioning
confidence: 99%